Effects of different doses of intranasal dexmedetomidine on related complications and parents' satisfaction in anesthetized children: a systematic review - Wei Hu; Ming Wang; Fei Sun (BMC, 2024)
Abstract Background Agitation/delirium is commonly seen in children after anesthesia, and a proper dose of dexmedetomidine can prevent this complication. This study aimed to investigate the effects of different doses of Dexmedetomidine (DEX) on agitation/delirium and other complications in anesthetized children, providing clinical evidence for dose recommendations of DEX. Methods This study was conducted based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). A systematic search was conducted in the Cochrane Library, PubMed, Web of Science, and EMBASE. Two independent researchers performed literature screening, data extraction, and assessed the methodological quality. Data analysis was conducted using R and STATA 16.0. Results In the final analysis, 20 randomized controlled trials (RCTs) involving 2521 children were included. The results showed that in comparison to normal saline, 1 µg/kg, 1.5 µg/kg, and 2 µg/kg intranasal DEX significantly reduced the incidence of post-anesthetic emergence agitation in children with the most effective dose being 2 µg/kg (SUCRA = 0.91). Compared with normal saline, 1 µg/kg, 1.5 µg/kg, and 2 µg/kg intranasal DEX reduced patient's need for postoperative analgesia, with the most effective dose being 1.5 µg/kg (SUCRA = 0.78). However, 1 µg/kg DEX performed the best in reducing Pediatric Anaesthesia Emergence Delirium (PAED) Scale score (SUCRA = 0.88). Conclusion Compared with normal saline, intranasal administration of 2 µg/kg DEX and 1.5 µg/kg DEX are the optimal doses to reduce the incidence of agitation and the need for postoperative pain relief in children under general anesthesia. Given effectiveness and safety, intranasal use of 1 µg/kg DEX appears to be the most effective dosage for anesthetized children.